Assessing salt tolerance, phenotypic traits and genetic diversity in chickpea (Cicer arietinum L.) accessions using SSR markers - Zevar H. Tolibova (22686713) (2025)
Soil salinity is a major abiotic stress that severely limits chickpea (Cicer arietinum L.) productivity, especially in semi-arid regions such as Uzbekistan. This study evaluated 50 chickpea accessions under optimal and naturally saline field conditions, combining phenotypic analysis with SSR marker-based genetic diversity and in silico mapping to identify tolerant germplasm. Significant phenotypic variation was observed and several genotypes (e.g., ‘Malxotra’, ‘Guliston’, ‘Lazzat’, ‘Iftikhor’, ‘SSA−2’, ‘SSA−10’) were identified as highly salt-tolerant. Under salinity stress, seed weight per plant showed strong positive correlations with pod number (r = 0.63***) and seed number (r = 0.69***). Genetic diversity assessed using 37 polymorphic SSR markers revealed 148 alleles, averaging 3.8 alleles per locus. The mean polymorphism information content (PIC) was 0.37 (ranging from 0.21 to 0.63), with the highest expected heterozygosity (He = 0.69) detected for markers H1C22, STMS22, and TR20. In silico analysis localized these markers to salt-tolerance associated regions on chromosomes, identifying candidate genes encoding LEA proteins, ion transporters, kinases, and redox regulators. These fundings, particularly the identified tolerant genotypes and associated markers, provide a valuable foundation for marker-assisted selection and the development of salt-tolerant chickpea cultivars.